Kinetic evidence for the influence of subsurface oxygen on palladium surfaces towards CO oxidation at high temperatures - Gopinath, Chinnakonda S.; Thirunavukkarasu, Kandasamy; Nagarajan, Sankaranarayanan (Chemistry-an Asian Journal, 2009)
Transient state kinetics of the catalytic oxidation of CO with 0, on Pd-surfaces has been measured under isothermal conditions by using a molecular beam approach. Systematic studies were carried out as a function of reaction temperature and CO+O(2) composition. With sufficient kinetic evidence, we have demonstrated the positive influence of subsurface oxygen towards CO-adsorption and oxidation to CO, at high temperatures (600-900 K) on Pd-surfaces, and the likely electronic nature of the surface changes with oxygen in the subsurface. These studies also provide a direct proof for CO-adsorption with a significantly reactive sticking coefficient at high temperatures on Pd-surfaces exhibiting a significant subsurface O-coverage.
Keywords: Adsorption; kinetics; Oxidation; Palladium; surface analysis

Kinetics of nitric oxide adsorption on Pd(111) surfaces through molecular beam experiments: a quantitative study - Nagarajan, Sankaranarayanan; Thirunavukkarasu, Kandasamy; Gopinath, Chinnakonda S.; Prasad, Sudarsan D. (Journal of Physical Chemistry C, 2011)
A detailed kinetic picture derived by molecular beam studies of the adsorption-desorption of the NO/Pd(111) system is presented. Numerical simulations and detailed kinetic analysis show that the precursor state model of adsorption provides a valid picture of the sticking coefficient variation with surface coverage, especially at low temperatures. At higher temperatures, the precursor model gives way to the Langmuir molecular model of adsorption. All the parameters of the precursor state model have been quantified. Temperature programmed desorption (TPD) studies further show that there is a slight repulsive interaction between adsorbed NO molecules and there is only a negligible fraction of dissociated molecules on the surface for temperatures less than 500 K, as the Pd(111) surface is defect free. A Bragg-Williams (BW) lattice gas model with repulsive interactions, within the framework of mean field approach (MFA), is shown to describe the TPD spectra reasonably well.